ETHANOLIC EXTRACT OF PAPAYA LEAVES (CARICA PAPAYA) AND ITS FRACTIONS HAVE NO POTENTIAL CYTOTOXICITY ON T47D CELLS - Yuliani, Ratna; Syahdeni, Faisal (Universitas Muhammadiyah Surakarta, 2020)
Breast cancer is one type of cancer that causes high mortality rate in women. Plants produce secondary metabolites with a wide range of activity, one of which is as an anticancer. This research was conducted to investigate the cytotoxic effect of ethanolic extract of papaya leaves (Carica papaya) and its fractions on T47D cell line. Extraction of the natural compounds from papaya leaves was carried out by soaking the leaf powder in 96% ethanol followed by filtration and solvent evaporation. Liquid partition was done to obtain hexane, ethyl acetate, and water fractions. The cytotoxicity of the extract and the fractions was tested using MTT assay. Identification of chemical compounds in the ethyl acetate fraction was conducted using a thin layer chromatography method that used silica gel GF 254 as the stationary phase and acetone and hexane (4:6) as the mobile phase. The MTT assay result shows that the extract does not inhibit the growth of T47D cells. The viability of T47D cells can be reduced by the hexane, ethyl acetate, and water fractions with IC50 values of 2,231.30, 557.33, and 2,112.81 ?g/mL, respectively. The ethyl acetate fraction contains flavonoids, alkaloids, phenolics, and terpenoids. The ethanolic extract of papaya leaves and the fractions has no potential cytotoxicity on T47D cells due to high IC50 values.